Screening adolescents for substance use: The role of NPs in school settings. Issue 5 (19th May 2016) - Alayan, Nour; Shell, Lynn
Abstract : Abstract: NPs have a key role in screening for adolescent substance use in school settings. This article provides evidence-based information on the prevalence and consequences of adolescent substance use, discusses standardized substance use screening and brief interventions using the CRAFFT tool, and suggests relevant practice and policy implications.